SIMULATION ANALYSIS AND STRUCTURE OPTIMIZATION OF STAMPING ROBOT ACTUATOR BASED ON ABAQUS - FU Min; WANG JinXin; SU HaiLong; WANG Kai (Jixie qiangdu)
In the automatic stamping production,the stamping robot completes the clamping and conveying of workpiece through the actuator,and the positioning of the actuator is completed by the mutual cooperation of electrical control and stopper.During the auxiliary positioning of the stopper,the actuator will collide with the stopper,which has an adverse impact on the stamping production. Therefore,the impact simulation analysis and structural optimization design of the actuator are carried out.The 3 D solid model of the actuator was established by UG NX8. 5 software,and imported into ABAQUS software for fem simulative analysis to obtain the clamping force,acceleration and tilt angle and other parameters of the workpiece. From the analysis of simulation results,it can be seen that the clamping force on the workpiece is zero and the peak value is large,the acceleration of the workpiece changes sharply in a short time,and the tilt Angle after collision is large. Aiming at the above problems,the optimal design of the actuator is carried out,which effectively reduces the impact of collision on the actuator and improves the efficiency of stamping production.